Oncogenic potential of Salmonella infection: a short review - Alhussainy, Abrar; Al-Humadi, Hussam W.; Al-Saigh, Rafal J. (Pharmakeftiki, 2025)
Salmonella infections, whether typhoidal or non-typhoidal, represent a major global health burden. While acute infections primarily manifest as gastroenteritis, chronic infections have been increasingly associated with severe long-term complications, including inflammatory bowel disease, gallbladder cancer, and colorectal cancer. Emerging evidence indicates that Salmonella infections may promote tumorigenesis through multiple mechanisms, such as chronic inflammation, DNA damage, and the manipulation of host cell signalling pathways. Specifically, Salmonella effector proteins, including AvrA, SopE, SopE2, and SopB, have been shown to play a critical role in activating oncogenic pathways such as Wnt/β-catenin, PI3K/Akt, and MAPK, which drive cellular transformation and tumour progression. Additionally, Salmonella infection can disrupt the gut microbiome, leading to dysbiosis, which may further contribute to cancer risk. Environmental factors, lifestyle choices, and genetic predispositions also modulate the risk of developing these cancers. This short review highlights the urgent need for further research in order to unravel the complex interactions between Salmonella infections, host factors, and cancer development, with the goal of improving prevention, early detection, and therapeutic strategies.